Des dispositifs de connaissances territoriales pour (re)penser les relations villes-montagnes des métropoles alpines - Emmanuel Roux (Revue de Géographie Alpine)
This paper proposes to show how the territorial cognitive devices, as systems of representations and expressions of contemporary problems, are indicative of the logics of “alpine metropolitan cities” constructions and of the evolution of relationships city-mountain. From the analysis of a corpus of diagnostics of territories and interviews carried out with elected officials and technicians of an alpine metropolis, we will show that the cognitive devices express in the first place both the logics of juxtaposition and of interweaving of the urban and mountainous issues. Secondly, they express the prospects and pitfalls of integrating the mountain municipalities into metropolitan cities. Finally, they reveal the emergence of adaptive devices, of intermediation aimed at facilitating the elaboration of alpine metropolitan cities with reciprocally relationships city-mountain.